Use of nitrogen management products and practices to enhance yield and nitrogen uptake in no-till corn and grain sorghum - Weber, Holly S. (Kansas State University, 2010)
Nitrogen fertilizers play an essential role in agricultural production in Kansas, particularly in row crops such as corn (Zea mays L.) and grain sorghum (Sorghum bicolor (L.) Moench). A good portion of the corn and grain sorghum grown in Kansas is typically grown using no-till production systems. These systems leave a large amount of surface residue on the soil surface, which can lead to ammonia volatilization losses from surface applied urea-containing fertilizers and immobilization of N fertilizers placed in contact with the residue. Leaching and denitrification can also be a problem on some soils. Current nitrogen prices, as well as concerns over environmental stewardship, are forcing producers to make smarter choices in the fertilizer products used as well as when and how the materials are applied, to optimize their nitrogen use efficiency. A common practice throughout Kansas is to apply N fertilizers prior to planting, sometimes up to 6 month prior to planting. What affect does this practice have on nitrogen availability to the growing crop? Current Kansas State University (KSU) soil test fertilizer recommendations assume 50% nitrogen use efficiency. This means of every pound of nitrogen applied only half will be utilized by the plant and turned into valuable grain. Possible solutions to help increase nitrogen use efficiency are the use of nitrogen additives which are currently on the market and claim to reduce nitrogen loss through denitrification and volatilization as well as the use of timing and application of fertilizers to further increase nitrogen use efficiency. The objective of this study is to evaluate different N fertilizer products, as well as additives and application practices and determine whether specific combinations can improve yield and N use efficiency of no-till corn and grain sorghum. The long-term goal of this study is to quantify some of these relationships to assist farmers in selecting specific combinations that could enhance yield and profitability. In this study five tools for preventing N loss were examined: fertilizer placement, or placing N below the soil surface or in bands on the residue-covered soil surface to reduce immobilization and/or volatilization; use of a urease inhibitor Agrotain (NBPT) that blocks the urease hydrolysis reaction that converts urea to ammonia and potentially could reduce ammonia volatilization; the use of a commercially available additive, Agrotain Plus, that contains both a nitrification inhibitor (DCD) and a urease inhibitor to slow both urea hydrolysis and the rate of ammonium conversion to nitrate and subsequent denitrification or leaching loss; use of a commercial product NutriSphere-N, which claims urease and nitrification inhibition; and the use of a polyurethane plastic-coated urea to delay release of urea fertilizer until the crop can use it. The ultimate goal of using these practices or products is to increase N uptake by the plant and enhance yield. An important measurement that was developed for this research was the use of a greenleaf firing index which used the number of green leaves below the ear at pollination as a key measurement in determining the effectiveness of fertilizer placement, application method, application timing and the use of nitrogen additives. If significant differences in lower leaf nitrogen stress are found, the potential exists to further develop this index and correlate differences observed with key parameters of nitrogen uptake such as ear-leaf nitrogen concentration, total nitrogen uptake and grain yield. Results observed from this research show that the potential to increase nitrogen use efficiency and reduce nitrogen loss do exist with the use of certain nitrogen additives, application methods and application timing. When conditions are conducive for nitrogen loss the use of currently available tools to protect nitrogen from volatilization, immobilization and/or denitrification loss significantly increased yields in the corn experiments. Results from the grain sorghum research indicate that when N losses limit yield, the use of products and practices enhance yield. In locations where nitrogen loss is minimal or low yields limit nitrogen response, the use of these practices was not found to be helpful.
Keywords: Nitrogen use efficiency; controlled release fertilizers; NBPT; Green leaves below the ear; Nutrasphere-N; Nitrogen Placement; Agriculture, Agronomy (0285)